Understanding the condition of disease prevention and control workforce by disciplines, duties, and work stress during the COVID-19 pandemic: A case from Beijing disease prevention and control system - Mao, Ayan; Yang, Yujie; Meng, Yueli; Xia, Qianhang; Jin, Shuyan; Qiu, Wuqi (Frontiers in Public Health, 2022)
Objective The duties and work stress of staff during the COVID-19 pandemic are analyzed to provide a scientific basis for workforce allocation in the disease prevention and control (DPC) system. Method The cross-sectional survey was made in April–May 2021 on professional staff (a total of 1086) in the Beijing DPC system. Assuming that the over load work stress is brought by incremental duties and cross-discipline task, a binary logistic regression model is constructed. Results 1032 staff were engaged in COVID-19 prevention and control works, and they assumed a total of 2239 duties (2.17 per person). The analysis of work stress reveals that the Public health discipline (P) group and N-Public health discipline (N-P) group have similar proportions in view of full load work stress and the P group shows a higher proportion of over load work stress than the N-P group. The duty quantity and cross-discipline task are statistically positively correlated with the probability of over load work stress. Conclusion The front-line staff in the DPC system involved in the COVID-19 prevention and control primarily fall in the category of Public Health and Preventive Medicine discipline. The P group assumes the most duties, and the N-P group serves as an important cross-complement. The study results indicate that the prevention and control of same scale epidemic require the duty post setting at least doubled than usual. As to workforce recruitment, allocation and reserve in respect of DPC system, two solutions are optional: less addition of P staff, or more addition of N-P staff. A balance between P and N-P staff that enables the personnel composition to accommodate to both routine DPC and unexpected epidemic needs to be further discussed.